Role of primary and secondary surfactant layers on the thermal conductivity of lauric acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of Physical Chemistry C, 2016)
Lauric (dodecanoic) acid coated magnetite nanoparticles with different amounts of primary and secondary surfactant layers on the surface of the nanoparticles have been synthesized. Two sets of the surfactant coated nanoparticles are prepared; one with a comparable amount of primary surfactant and the other with a comparable amount of secondary surfactant. Nanofluids are prepared by dispersing the surfactant coated nanoparticles in toluene. Stability of the nanofluids is found to decrease with increasing amount of secondary surfactant on the surface of the nanoparticles, due to the increased hydrophilic nature of the particles in the nonpolar solvent. Thermal conductivity and viscosity of the nanofluids are found to increase with increasing amount of the secondary surfactant layer on the surface of the nanoparticles. The enhanced thermal conductivity for fluids with particles having a larger amount of secondary surfactant is ascribed to the lower dispersibility of the particles in toluene due to the exposure of the acid group of the surfactant to the hydrophobic solvent, leading to aggregation of the particles. Only a small increase in the thermal conductivity is observed for fluids with a larger amount of primary surfactant on the surface of the nanoparticles due to the increased dispersibility owing to the large number of hydrophobic tail groups of the surfactant. A larger enhancement in the thermal conductivity is observed in the presence of a small magnetic field for the fluids containing particles with a lower amount of the secondary surfactant. The overall results suggest that the thermal conductivity of the nanofluids depend on the amount and nature of the primary and secondary surfactants on the dispersed particles which in turn determine the interaction between the base fluid and the surfactant and therefore the dispersibility and stability of the nanofluids.

Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity

Review of the recent progress on thermal conductivity of nanofluid - Lenin, Ramanujam; Joy, Pattayil Alias; Bera, Chandan (Journal of Molecular Liquids, 2021)
Thermal properties of nanofluids are very well investigated by the global research community for their various applications. The dispersion and stability of the nanoparticles in the base fluid are the essential requirements for the efficient utilization of nanofluids in many applications. The interfacial layer plays a crucial role in the dispersion, stability, and heat transfer properties of the nanofluid. The heat transfer property of the nanofluids is mainly influenced by the heat transfer properties at the particle-fluid interface. The thickness and thermal conductivity of the interfacial layer are the crucial factors that decide the heat transfer at the interface, and the difficulties in the determination of these factors limits the progress of the research. In this review article, the experimental studies on the thickness and thermal conductivity of the interfacial layer are reviewed briefly. The effect of interfacial the layer on the nanoscale mechanisms and thermophysical properties of nanofluids are reviewed. The effect of various tunable parameters on the heat transfer properties of the interfacial layer is also reviewed. This review will be beneficial for fine-tuning nanofluid's thermal properties and their commercial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Interfacial layer; Interfacial thermal conductance; Nanofluid; Surfactants; Thermal conductivity